A NEW SOLUTION FOR OLD PROBLEMS IN BRAZIL: CROPLIVESTOCK ROTATIONS WITH ZERO TILLAGE AS A SUSTAINABLE LAND MANAGEMENT TOOL - John N.Landers,; Jason Clay; Joseph Weiss (Sociedade & Natureza)
Land clearing has been the traditional tool for creating greater agricultural production since time began. All who consume the products of the land, in whatever form, are part of the sacrifice, willing or not, of biodiversity to generate sustenance and wealth (Declaration of Madrid, 2001). The farmer is omnipresent in areas which produce food and fibre and in many where timber is a product ; he should be encouraged to become a “steward of the land”, receiving environmental services payments for this responsibility. These are not subsidies, first because the off-farm benefits to society of ZT adoption (achieved, overwhelmingly, at the farmer´s expense) generate huge social transfers and, second, the WTO regulations do not classify these payments as such. The mitigation potential of land use intensification with integrated ZT crop x livestock systems (ICLZT), can vary between 0.8 and 2.5 ha of reduced demand for land clearing for each hectare in the system. By using a ZT crop ley for two to four years, the cost of pasture renovation is defrayed and pasture carrying capacity is trebled, from an average of about 0.7 animal units (AU)/ha to over 2 AU/ha. Both historical data surveyed and five spreadsheet models of real farms developed in this study, substantiate this. The study also shows higher net present value (NPV) and internal rate of return (IRR) values accompanying this new technology. Brazil has now established a national programme for ICLZT. Financial and other incentives, such as farmer and technician training, good technical backstopping from on-farm-research and preferential access to credit, are required to overcome the initial risk of change and incremental investments required to adopt the new technology. Recommendations are made for a fiscal package which emphasizes the “carrot” approach, but which sharpens the “stick”, when necessary. Also proposed are international credit projects for large-scale adoption of ICLZT systems.